Egypt – a return to a balanced gas market? - Ouki, M (Oxford Institute for Energy Studies, 2018)
In 2015, Egypt became a net gas importer. This unfortunate, but not unexpected, situation was the result of a decline in Egypt’s indigenous natural gas production combined with a rapidly rising domestic gas demand driven mainly by large energy price subsidies. Major changes are presently taking place on the gas supply side which are significantly impacting the country’s natural gas balance. The Egyptian government is also carrying out energy price reform measures to reduce gas demand growth and the financial burden of price subsidies. But, without the continued implementation of consistent and integrated energy demand-side management and reform measures, Egypt could again be exposed to an unpleasant gas supply surplus/deficit cycle. The quick answer to the question posed in this paper’s title ‘Egypt – a return to a balanced gas market?’ could be: yes, but not for long. However, this short statement would not do justice to the considerable efforts deployed by all the relevant stakeholders in relaunching Egypt’s hydrocarbon sector. It would also ignore the fact that the answer is only based on current publicly available data and information on both the supply and demand sides.